In Vitro Hepatoprotective and Human Gut Microbiota Modulation of Polysaccharide-Peptides in Pleurotus citrinopileatus - Huang, Yihua; Gao, Yi; Pi, Xionge; Zhao, Shuang; Liu, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Pleurotus citrinopileatus, a golden oyster mushroom, is popular in Asia and has pharmacological functions. However, the effects of polysaccharide-peptides extracted from Pleurotus citrinopileatus and underlying mechanism on digestive systme have not yet been clarified. Here, we determined the composition of two polysaccharide-peptides (PSI and PSII) from P. citrinopileatus and investigated the protective effects of on hepatoprotective and gut microbiota. The results showed that PSI and PSII were made up of similar monosaccharide moieties, except for the varying ratios. Furthermore, PSI and PSII showed that they have the hepatoprotective effects and significantly increased the viabilities and cellular total superoxide dismutase activities increased significantly in HepG2 cells. Intracellular triglyceride content and extracellular alanine aminotransferase and aspartate transaminase contents markedly decreased following treatment with 40 and 50 μg/mL PSI and PSII, respectively. Moreover, PSI and PSII activated the adiponectin pathway and reduced lipid accumulation in liver cells. PSI and PSII elevated short-chain fatty acid concentrations, especially butyric and acetic acids. 16S rRNA gene sequencing analysis showed that PSI promoted the relative abundances of Bifidobacteria, Lactobacillus, Faecalibacterium, as well as Prevotella generas in the gut. PSII markedly suppressed the relative abundances of Escherichia-Shigella and Bacteroides generas. We speculate that the PSI and PSII play a role through liver-gut axis system. Polysaccharide-peptides metabolize by gut microbiota to produce short-chain fatty acids (SCFAs) and in turn influence liver functions.